Behavior of the southernmost San Andreas fault during the past 300 years - Sieh, Kerry (2012)
Surficial creep occurs at low rates along the Coachella Valley segment of the San Andreas fault, which has not produced a large earthquake during the period of historical record. Geodetic data indicate, however, that the crust adjacent to this segment of the San Andreas fault is accumulating strain at a high rate. Furthermore, neotectonic and paleoseismic data indicate that the fault does produce very large earthquakes every two to three centuries. In view of its long-term behavior, the occurrence of creep along the surficial trace of the fault in the Coachella Valley is of particular interest. Along two short reaches of the San Andreas fault in the Coachella Valley, measurements of offset geological deposits and man-made structures and from alignment arrays and creep meters show that slip rates of 2–4 mm/yr near Indio and near the Salton Sea have persisted for the past three centuries. This slow aseismic surficial creep is not a transient precursor to seismic failure of this segment of the fault. We suggest that the Coachella Valley segment of the San Andreas fault creeps in its upper few kilometers. This behavior may be due to tectonically induced high pore pressures in the coarse sediments that abut the fault.